(untitled) (Research, Society and Development, 2023)
Objective: To describe the epidemiological profile of Alzheimer’s disease in Brazil between 2013 and 2022. Methods: This is an exploratory, time-series study of epidemiological data on Alzheimer’s disease in the Brazilian population. Data were obtained through the SUS Information System (DATASUS). Results: It was verified that there were 14,024 hospitalizations due to Alzheimer’s Disease in Brazil between January 2013 and December 2022 and the most confirmed Brazilian region was the Southeast. In addition, it was possible to observe that the most trained age group was 80 years or older, with 8,168 cases, followed by the population aged 70 to 79 years, with 4,061 hospitalizations. With regard to sex and color, white women were the most affected. There were 152,891 deaths, most of which occurred in the southeastern region of the country. The average hospital stay rate was 22.9 days, the average hospital stay was R 1,754.75 and the total amount spent on Alzheimer’s in the analyzed period was R 24,608,616.49. Conclusion: In short, it is possible to infer that Alzheimer’s disease has a high incidence in Brazil, especially in the Southeast region. Female patients, white, aged 70 years or older are the most dependent. Despite being a disease of late onset in most cases, it causes damage to the quality of life of patients, as it causes impairment of higher cognitive functions, especially loss of memory of recent events.